Meneladani Karakter Sudiro dalam Buku "Sudiro Pejuang tanpa Henti" - Ratumas Nurul Hikmah; Anny Wahyuni; Budi Purnomo (Historia Madania: Jurnal Ilmu Sejarah, 2021)
Historically, the Indonesian independence cannot be separated from figures who struggle and sacrifice for the country. One of the figure is Sudiro. Sudiro is a teacher as well as a politician who fights for the nation with high spirit, duties and responsibilities even he was occassionnaly at risk. This article deals with a biographical study of Sudiro as discussed in a book “Sudiro Pejuang tanpa Henti”,  the objective of the research is to find the moral values which can be taken as an example for the present generation. The method used in this research is historical research methodology with several stages such as heuristics, criticism, interpretation, and historiography. After analyzing the book and some sources, the findings of this article show that some character of sudiro are religious, discipline, hard worker, democratic, having nationalism, a good reader and responsible.    Keywords: Sudiro, Indonesian figure, biographical study.